Socio-Emotional Drivers of Youth Unemployment : The Case of Higher Educated Youth in Sudan - De Martino, Samantha; Farfán, Gabriela; Gayoso, Lyliana; Osman, Eiman (World Bank, Washington, DC, 2022)
This study seeks to contribute to the existing literature in Sudan by analyzing psychological, social, and behavioral drivers of youth employment in combination with key structural issues identified in the country. Our analysis is based in existing literature on the structural problems that Sudanese youth face to accessing the labor market and uses a novel dataset to examine the factors that determine youth’s career aspirations as well as the factors that serve as barriers to achieve their career aspirations. In addition, the study explores the role of mindsets and soft skills, both as direct determinants of labor market outcomes as well as indirect determinants through their impact on aspirations. Specifically, we measure mental health (anxiety), core self-beliefs, and job-relevant soft skills that moderate the way individuals manage and interact socially in the labor market. Core self-evaluation beliefs determine the way individuals perceive their own basic capabilities, and soft skills are a set of learned, realized behaviors that allow individuals to effectively manage inter- and intrapersonal situations. The aim of this study is to provide a deeper and more comprehensive understanding of the youth unemployment challenge to help identify potential cost-effective interventions that support youth’s job search and employability in Sudan.